2019
DOI: 10.1056/nejmoa1813730
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Progesterone in Women with Bleeding in Early Pregnancy

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 138 publications
(159 citation statements)
references
References 18 publications
5
133
0
8
Order By: Relevance
“…The New England Journal of Medicine article on the PRISM trial noted a 3% increase in live birth rate with vaginal micronized progesterone, but suggested it was a negative result, as the P value associated with this finding was .08. 10 However, our interpretation of the PRISM trial in this review takes into account the totality of available evidence, suggesting a potential role for progesterone for women at high risk of a miscarriage. We propose the apparent discordance between the published New England Journal of Medicine manuscript 10 and our interpretation relates to the issue of statistical inference vs scientific inference.…”
Section: Statistical and Scientific Inferencesmentioning
confidence: 99%
See 3 more Smart Citations
“…The New England Journal of Medicine article on the PRISM trial noted a 3% increase in live birth rate with vaginal micronized progesterone, but suggested it was a negative result, as the P value associated with this finding was .08. 10 However, our interpretation of the PRISM trial in this review takes into account the totality of available evidence, suggesting a potential role for progesterone for women at high risk of a miscarriage. We propose the apparent discordance between the published New England Journal of Medicine manuscript 10 and our interpretation relates to the issue of statistical inference vs scientific inference.…”
Section: Statistical and Scientific Inferencesmentioning
confidence: 99%
“…10 However, our interpretation of the PRISM trial in this review takes into account the totality of available evidence, suggesting a potential role for progesterone for women at high risk of a miscarriage. We propose the apparent discordance between the published New England Journal of Medicine manuscript 10 and our interpretation relates to the issue of statistical inference vs scientific inference. Statistical inference focuses on hypothesis testing.…”
Section: Statistical and Scientific Inferencesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, the authors have combined progesterone with progestogens; however, they are not the same, in the same way that estrogen and diethylstilbestrol are not the same. Vaginal micronised progesterone, which we used in our large and high‐quality trials (the PROMISE 2 and PRISM 3 trials), has an identical molecular structure to natural progesterone but the other drugs included in this review do not (Table 1). We chose to study vaginal micronised progesterone, as it is identical in structure to natural progesterone, and the available evidence and expert opinion suggested that this is least likely to cause harm.…”
Section: Drug Chemical Structurementioning
confidence: 99%